Factors associated with vocal fry among college students. (3rd April 2018) - Cantor-Cutiva, Lady Catherine; Bottalico, Pasquale; Hunter, Eric
Abstract: Purpose: Vocal fry is increasingly used in everyday speech. The purpose of this study was to identify associated factors of vocal fry among young US college-age students.Methods: Forty college students participated in a cross-sectional study. Participants produced speech under nine different room acoustic conditions (simulated). The recorded speech was perceptually evaluated by three speech-language pathologists. Multivariate logistic regression analysis was used to identify variables (individual, environmental) associated with the perceptual assessment of vocal fry.Results: A high occurrence of perceptually identified vocal fry was identified among college students. Two factors were significantly associated with lower occurrence of perceptually identified vocal fry: one individual (sporadic consumption of caffeinated beverages) and one environmental factor (speaking in an environment with background noise).Conclusions: Similar to modal phonation, fry-like phonation seems to be influenced by individual and environmental factors. Therefore, clinicians interested in including this technique as part of their intervention programs may take into account the caffeine consumption and the background noise conditions of the room where the therapy will take place in order to facilitate the production of fry-like phonation.